Morpho-anatomical, phytochemical and chromatographic characterization of Gomphrena perennis var. Perennis L. - Bonilla Bonilla, Adriana Milena (2017)
Gomphrena perennis var. perennis L. "flower of paper" or "always alive of the field" (Amaranthaceae) is a perennial species distributed in South America, mainly Paraguay, Brazil, Argentina and Uruguay [5]. It was used in traditional medicine as a stomach purifying, emollient, and diuretic [3]. Its presence has increased in the last decade because it behaves as a weed tolerant to the herbicide Glyphosate (Round-Up®), widely used in the production system of direct seeding. The objective of this work was to describe morpho-anatomically the vegetative organs: root, stem and leaf of G. perennis as well as characterize phytochemistry and chromatographically the extracts of its aerial part. The vegetal material was herborized, botanically identified and analyzed in La Plata, Argentina. Epidermal studies were performed using the diaphanization technique [1], the observations and microphotographs of the evaluated organs were carried out with optical microscope Nikon Photolab II and the study of waxes and foliar ornamentations by scanning electron microscope (SEM) Jeol JSM-35CF. The aerial part was extracted with 70 ° Ethanol by maceration in cold and with solvents of increasing polarity (Dichloromethane, Ethyl acetate, methanol). These extracts are analyzed by characterization reactions [2] and thin layer chromatography (TLC) in mobile phases suitable for each of the main phytochemical groups [4]. The methanolic and hydroalcoholic extract was investigated using HPLC-UV. Morpho-anatomical studies revealed anomalous secondary growth of the herbaceous stems of G. perennis with abundant trichomes, a tuberous root system and a structure called xylopodium with the ability to regrow when generating aerial branches of adventitious origin. Its leaves are simple, with Kranz structure of atriplicoide type, which indicates that G. perennis has C4 metabolism and it is covered by abundant multicellular trichomes, which have deposits of epi-cuticular waxes called teicodes. Phytochemical tests established the presence of polyphenols, alkaloids, steroids and saponins. The TLC investigation allowed describing the chromatographic profiles of the extracts relative to markers of the main phytochemical groups. The HPLC chromatographic profiles of the methanol and hydroalcoholic extracts were also obtained. All of the above contributes to the botanical and phytochemical knowledge of the Argentinean flora and specifically of G. perennis.